Media Engklek Gunung untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar Negeri 1 Payaman - Mia Novita Annur; Sumarwiyah Sumarwiyah; Imaniar Purbasari (EduBase : Journal of Basic Education, 2020)
The purpose of this research is to improve the students learning outcomes by the applying EKU media in fifth grade students of the SDN 1 Payaman Kudus in a academy year 2019/2020. The approachment of this research is classroom action research wich consist of two cycles. Each cycle consists of two confluence and four phase, they are: planning, action implementation, observation, and reflection. the subject and data resources were teacher and students which consists of 29 students. The data collection techniques used interview, observation, documentation and test. The validaty data techniques used Expert Judgement. The resech data analysis used quantitative and qualitative. The result of this research show that the student learning outcomes improved in each cycle. Percentage of classical students learning outcome the percentage of classical completeness in outcomes learning social knowledge scincence in the first cycle 44,82% with an average 64,82 and in cycle 82,76% with an average 82,58. In Indoneisan in the first cycle 58,62% with an average 70,51 and the second cycle 75,87% with an average 83,63. While in the outcomes of student learning in the aspect of skills in the first gained 55,34% and increased in the second with 78,20%. Based on the research result, it can be concluded that the application of EKU media can to improve students learning outcomes in fifth grade students of the SDN 1 Payaman Kudus in a academy year 2019/2020. Abstrak Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa melalui penerapan media Engklek Gunung (EKU) pada siswa kelas V SDN 1 Payaman Kudus tahun ajaran 2019/2020. Pendekatan penelitian ini adalah penelitian tindakan kelas yang terdiri dari dua siklus. Pada setiap siklusnya terdiri dari dua pertemuan dan empat tahapan yaitu: perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek dan sumber data adalah guru dan siswa yang berjumlah 29 siswa. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi, dan tes. Teknik uji validasi data yang digunakan adalah Expert Judgement. Teknik analisis data yang digunakan adalah kuantitatif dan kualitatif. Hasil penelitian ini menunjukan bahwa hasil belajar siswa meningkat pada setiap siklusnya. Persentase ketuntasan klasikal hasil belajar siswa aspek pengetahuan IPS pada siklus I 44,82% dengan nilai rata-rata 64,82 dan pada siklus II 82,76% dengan rata-rata 82,58. Pada Bahasa Indonesia pada siklus I 58,62% dengan rata-rata 70,51 dan pada siklus II 75,87% dengan rata-rata 83,63. Sedangkan pada hasil belajar siswa aspek keterampilan pada siklus I memperoleh 55,34% dan mengalami peningkatan pada siklus II 78,20%. Berdasarkan hasil penelitian yang diperoleh, dapat disimpulkan bahwa penerapan model EKU dapat meningkatkan hasil belajar pada siswa kelas V SDN 1 Payaman tahun ajaran 2019/2020.